Effects of web-based teaching on Arabic reading comperhension and motivation of female Jordanian basic school students - Al-Khasawneh, Sani Sami (2013)
The purpose of this research was to investigate the effects of Arabic as first language Web-Based Teaching (AL1WBT) on female Jordanian basic school students’ reading comprehension achievement and motivation.This study applied a quasi-experimental design which was the non-equivalent design.The study sample consisted of 104 ninth grade students from Rouguih Bint Alrasool basic school was randomly selected from 85 government schools.The instruments employed werethe demographics questionnaire, the Arabic reading comprehension achievement tests and the Instructional Materials Motivation Scale (IMMS). Descriptive and inferential statistics were conducted to analyzethe collected data. Analysis of covariance (ANCOVA) was conducted to compare the students' overall reading comprehensions achievement based on the post-test and delayed post-test scores in the aspects of interpretive reading,critical reading and creative reading between AL1WBT and Experience Method (EM) groups while statistically controlled the pre-test effect. Paired sample t-test was conducted to compare the effect of AL1WBT and EM on the overall reading comprehension achievement of the students based on the pre-test, post-test and delayed post-test scores Independent samples t-test was used to compare the student’s overall motivation based on the post-test scores in the aspects of attention, relevance, confidence and satisfaction between AL1WBT and EM groups. This study found that the use of AL1WBT helped students performed significantly better in reading comprehension achievement in the aspects of interpretive reading, critical reading and creative reading. However, the effect of AL1WBT was found to decrease in delayed post-test after seven weeks. Finally, the study found that students using AL1WBT were significantly motivated in the aspects of attention, relevance, confidence and relevance than students using EM.